PEMUTUSAN KONTRAK IKATAN KERJA SAMA ANTARA RUMAH SAKIT SWASTA DENGAN BPJS KESEHATAN TERKAIT DENGAN KECURANGAN (FRAUD) BERUPA PENULISAN KODE DIAGNOSA YANG BERLEBIHAN/UPCODING - Kristanti Saraswati Ritonga (2020)
Termination of the contract of cooperation between the private hospital and BPJS Kesehatan related to fraud in the form of writing an excessive diagnostic code / upcoding, is clearly in accordance with contract law in Indonesia. This research is normative, namely research on legal principles, using a descriptive type of research, namely by describing the results of research in a complete and systematic manner on matters that are the subject of writing. The results and conclusions of the study that the termination of cooperation contracts between private hospitals and BPJS Kesehatan related to fraud in the form of writing excessive diagnostic codes /upcoding is in accordance with contract law in Indonesia. The basis for terminating this cooperation contract is in accordance with Article 1267 of the Civil Code. And the legal consequences for the parties to terminate the cooperation contract related to fraud in the form of writing excessive diagnostic codes / upcoding, regulated in Article 1243, Article 1267 and Article 1365 of the Civil Code. BPJS Kesehatan is expected to provide complete socialization to private hospitals regarding the substance of the cooperation contract with private hospitals. And the private hospital knows in detail the obligations that must be fulfilled in this cooperation agreement, especially related to fraud associated with writing an excessive diagnostic code / upcoding, which is carried out by the private hospital. The parties share this agreement in good faith.